On diagonal quasi-free automorphisms of simple Cuntz-Krieger algebras - Barlak, Selçuk; Szabó, Gábor (MATHEMATICA SCANDINAVICA, 2019)
We show that an outer action of a finite abelian group on a simple Cuntz-Krieger algebra is strongly approximately inner in the sense of Izumi if the action is given by diagonal quasi-free automorphisms and the associated matrix is aperiodic. This is achieved by an approximate cohomology vanishing-type argument for the canonical shift restricted to the relative commutant of the set of domain projections of the canonical generating isometries in the fixed point algebra.